Analisis Rantai Pasok Pengembangan Agroindustri MOCAF di Kabupaten Jember - Wibowo, Yuli; Herlina, Herlina; Soekarno, Siswoyo; Wiyono, Andi Eko; Aghata, Ola Riska Aprilia Intan (JURNAL AGROTEKNOLOGI, 2024)
Jember Regency has great potential in the agricultural sector, with cassava being one of its key commodities. Cassava can be developed into MOCAF (Modified Cassava Flour), produced through a fermentation process that modifies cassava cells using lactic acid bacteria. The development of the MOCAF agroindustry in Jember Regency has promising prospects due to the abundant availability of raw materials and increasing market demand. However, supply chain management optimization is necessary to ensure the effectiveness and efficiency of MOCAF agroindustry development. This study aims to generate effective and efficient strategy recommendations for developing the MOCAF agroindustry. The study uses the Interpretative Structural Modeling (ISM) method to determine the most dominant supply chain actors and the Analytical Hierarchy Process (AHP) method to determine the priority strategies for MOCAF agroindustry development. Based on the identification results, the MOCAF supply chain structure consists of four members: cassava farmers, collectors, MOCAF producers, and consumers. Farmers and cassava collectors act as suppliers of raw materials to producers, who then process them into MOCAF and sell them to consumers. The main actor in the supply chain is the consumer the party who determines the sustainability of the MOCAF agro-industry. Meanwhile, the most appropriate and prioritized supply chain development strategy is partnering with farmers to strengthen institutions within the supply chain. This strategy aims to improve the effectiveness and efficiency of relationships among supply chain actors, especially between the MOCAF agroindustry, farmers, and cassava collectors. This partnership is expected to ensure product quality, increase efficiency, stabilize, and even reduce the price of raw materials, which can increase the demand for MOCAF. Other strategies resulting from the AHP analysis are complementary to encourage the increase in MOCAF demand. Keywords: agroindustry, cassava, Jember Regency, MOCAF, supply chain